2011
DOI: 10.36076/ppj.2011/14/545
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Reasons for Failed Back Surgery Syndrome and Partial Results after Different Types of Surgical Lumbar Nerve Root Decompression

Abstract: Background: Despite the evident progress in treating vertebral column degenerative diseases, the rate of a so-called “failed back surgery syndrome” associated with pain and disability remains relatively high. However, this term has an imprecise definition and includes several different morbid conditions following spinal surgery, not all of which directly illustrate the efficacy of the applied technology; furthermore, some of them could even be irrelevant. Objective: To evaluate and systematize the reasons for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…Studies have shown that residual stenosis, arachnoiditis, and psychological effects may cause neuropathic pain after spinal surgery. [30][31][32] Duration of injury was also significantly associated with postoperative residual listhesis in the study cohort. More the duration, more is the fibrosis and fixation of deformity, leading to difficulty in achieving reduction.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown that residual stenosis, arachnoiditis, and psychological effects may cause neuropathic pain after spinal surgery. [30][31][32] Duration of injury was also significantly associated with postoperative residual listhesis in the study cohort. More the duration, more is the fibrosis and fixation of deformity, leading to difficulty in achieving reduction.…”
Section: Discussionmentioning
confidence: 90%
“…Manchikanti et al [ 35 ] reported that the prevalence of lumbar facet joint pain was 16% (95% CI, 9%–23%) in patients with recurrent pain after various spinal surgical interventions. Bokov et al [ 36 ] analyzed the reasons for persistent pain syndromes following surgical interventions for LDH, and found that facet joint pain was responsible for 23.1% of cases that underwent microdiscectomy. Although facet joint pain is estimated to be responsible for low back pain in 15%–45% patients, LFJOA has received far less study than other causes of back pain, such as disc degeneration [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the application of numeric scores is not standardized yet ( 8 ). Secondly, the results of those studies can be influenced by many irrelevant to the applied surgery causes, including the accuracy of diagnoses, socioeconomic, behavioral, psychological factors, sacroiliac joints dysfunction, and adjacent level degeneration ( 9 , 10 , 27 , 28 ). To avoid bias relevant to the application of subjective numeric scores, radiographic signs of PSL were used in the current study.…”
Section: Discussionmentioning
confidence: 99%